Tingling in tongue due to alprazolam and paroxetine-induced hypergabaergic activity - Önen Ünsalver, Barış; Evrensel, Alper; Ceylan, Mehmet Emin (The European Research Journal, 2019)
Paroxetine is a commonly used serotonin-reuptake inhibitor for the treatment of various psychiatric disorders. Available literature is sparse with cases of paresthesia that occur during withdrawal of paroxetine, there are fewer reports of paresthesia during the initiation. Here we report a case of panic disorder who experienced tingling of the tongue during the initiation phase of paroxetine, and whose paresthesia resolved only after the withdrawal of the drug. When paroxetine was introduced, the patient was already on alprazolam monotherapy. Therefore, the previously activated GABAergic state with alprazolam was probably further augmented with paroxetine. We suggest that the serotonin receptor supersensitivity related to panic disorder might have been a vulnerability factor for paresthesia, and the hypergabaergic state caused by alprazolam and paroxetine combination made the paresthesia evident in our case. This is the first report of a case with paresthesia in a combination of alprazolam and paroxetine. We might suggest that in patients who develop paresthesia during psychotropic use, the clinician’s first step might be to just decrease the dosage of the drugs before further clinical and laboratory evaluation of the patient for paresthesia.